TP53 mutations are associated with primary endocrine resistance in luminal early breast cancer. (14th November 2021) - Grote, Isabel; Bartels, Stephan; Kandt, Leonie; Bollmann, Laura; Christgen, Henriette; Gronewold, Malte; Raap, Mieke; Lehmann, Ulrich; Gluz, Oleg; Nitz, Ulrike; Kuemmel, Sherko; zu Eulenburg, Christine; et al.
Abstract: Background: Whereas the genomic landscape of endocrine‐resistant breast cancer has been intensely characterized in previously treated cases with local or distant recurrence, comparably little is known about genomic alterations conveying primary non‐responsiveness to endocrine treatment in luminal early breast cancer. Methods: In this study, 622 estrogen receptor‐expressing breast cancer cases treated with short‐term preoperative endocrine therapy (pET) from the WSG‐ADAPT trial (NCT01779206) were analyzed for genetic alterations associated with impaired endocrine proliferative response (EPR) to 3‐week pET with tamoxifen or aromatase inhibitors. EPR was categorized as optimal (post‐pET Ki67 <10%) versus slightly, moderately, and severely impaired (post‐pET Ki67 10%–19%, 20%–34%, and ≥35%, respectively). Recently described gene mutations frequently found in previously treated advanced breast cancer were analyzed ( ARID1A, BRAF, ERBB2, ESR1, GATA3, HRAS, KRAS, NRAS, PIK3CA, and TP53 ) by next‐generation sequencing. Amplifications of CCND1, FGFR1, ERBB2, and PAK1 were determined by digital PCR or fluorescence in situ hybridization. Results: ERBB2 amplification ( p = 0.0015) and mutations of TP53 ( p < 0.0001) were significantly associated with impaired EPR. Impaired EPR in TP53 ‐mutated breast cancer cases was independent from the Oncotype DX Recurrence Score group and was seen both with tamoxifen‐ and aromatase inhibitor‐based pET ( p = 0.0005 each). Conclusion: We conclude that impaired EPR to pET is suitable to identify cases with primary endocrine resistance in early luminal breast cancer and that TP53 ‐mutated luminal cancers might not be sufficiently treated by endocrine therapy alone. Abstract : Early recognition of endocrine resistance could be enabled by impaired suppression of proliferation after short‐term preoperative endocrine therapy (pET). Impaired endocrine proliferative response (EPR, post‐pET Ki67 ≥10%) sorts out cancers carrying TP53 mutations.